2015
DOI: 10.11113/jt.v77.5988
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHEMICAL SCREENING, TOTAL PHENOLIC AND TOTAL FLAVONOID CONTENT, AND ANTIOXIDANT ACTIVITY OF DIFFERENT PARTS OF Melastoma malabathricum

Abstract: Melastoma malabathricum Linn. commonly known as ‘senduduk’ in Malaysia, belongs to Melastomataceae family. The study was carried out to screen the phytochemicals present in methanol extract of leaf, flower, fruit, and stem and to evaluate the antioxidant activity, total flavonoid and total phenolic contents of these different parts. Phytochemical screening showed that all parts of this plant contained tannins, steroids, phenols and flavonoids. The flower extract was found to have highest total phenolic whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…It is one of the most abundant and diversified groups of pantropical families, having 4200 to 4500 species in 166 genera and approximately 1000 species predominantly cultivated in tropical Asia [4]. In Malaysia, particularly, the genus Melastoma consists of 22 species, 2 subspecies, and 3 varieties, which can be distinguished by the color of their flower petals, such as Melastoma malabathricum (dark-purple magenta), Melastoma decemfidum (white), and Melastoma hirta [4][5][6][7]. Studies have reported that members of this family have been used by practitioners of traditional medicines to treat diarrhea, pox scars, inflamed wounds, gastric ulcers, and diabetes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the most abundant and diversified groups of pantropical families, having 4200 to 4500 species in 166 genera and approximately 1000 species predominantly cultivated in tropical Asia [4]. In Malaysia, particularly, the genus Melastoma consists of 22 species, 2 subspecies, and 3 varieties, which can be distinguished by the color of their flower petals, such as Melastoma malabathricum (dark-purple magenta), Melastoma decemfidum (white), and Melastoma hirta [4][5][6][7]. Studies have reported that members of this family have been used by practitioners of traditional medicines to treat diarrhea, pox scars, inflamed wounds, gastric ulcers, and diabetes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that members of this family have been used by practitioners of traditional medicines to treat diarrhea, pox scars, inflamed wounds, gastric ulcers, and diabetes [8][9][10]. The phytochemistry of these plants has revealed numerous secondary metabolites or bioactive compounds, such as flavonoids and phenolic compounds [5]. Moreover, previous reports have shown the isolation of several flavonoids from M. decemfidum yields naringenin, kaempferol, kaempferol-3-O-D-glucoside, and kaempferol-3-O-[2 6 -di-O-p-trans-coumaroyl], which are responsible for their antioxidant activities [11].…”
Section: Introductionmentioning
confidence: 99%
“…A B Figure 1. Color of Senggani fruit extract with drying treatment, A: sun-drying treatment; B: oven drying treatment Phytochemical testing was utilized to determine quickly and simply whether a plant contains certain bioctive compounds or not (Danladi, et al, 2015). This test was performed employing chemical reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The qualitative screening of Melastomataceae leaf extracts has been widely reported [66][67][68]; however, to date, no available studies have reported on the biochemical properties of various parts of M. malabathricum L supplemented with FW compost and PK biochar. The results revealed the presence of flavonoids and phenols (Table 2).…”
Section: Discussionmentioning
confidence: 99%